Human ventilatory response to washed and unwashed cottons from different growing areas. - Petsonk, E L (1986)
Thirty volunteer subjects were exposed to controlled amounts of respirable dust generated by the carding of cotton in an experimental cardroom. Eighteen exposures each lasting six hours were performed while carding unwashed and washed cottons from the three major growing regions of the United States. Elutriated dust was analysed gravimetrically and was comparable (0.59 mg/m3 +/- 0.04) for all exposures. Spirometry was recorded before and after each exposure. California cotton resulted in a significantly smaller fall in FEV1 than cotton of the same grade from Texas or Mississippi. All washed cottons resulted in reduced declines when compared with unwashed cottons. For 17 subjects breathing zone personal total dust samples were analysed for airborne endotoxin and compared with the individual's pulmonary function response. A significant correlation between endotoxin exposure and acute decrease in FEV1 was seen. The effect on FEV1 per nanogram of airborne endotoxin was greater for Mississippi cotton than for cotton from the other regions. Airborne endotoxin appears to be an important determinant of acute pulmonary effects of cotton dust. Water washing of cotton results in reduced airborne endotoxin and less bronchoconstriction.